Pengaruh Komunikasi Interpersonal dan Komitmen Organisasi Terhadap Kinerja Karyawan pada Perusahaan Oto Bus PMS (Persatuan Motor Sekata) Pematangsiantar - Taufiq Nano Matondang; Patar Marbun; Dhian Rosalin (Economics, Business and Management Science Journal, 2023)
This study aims to assess and explain the influence of Interpersonal Communication and Organizational Commitment on Employee Performance at the Pematangsiantar Auto Bus Company, PMS (Sekata Motor Association). The study's population comprises employees at the PMS Auto Bus Company (Sekata Motor Association) in Pematangsiantar. The research data was obtained from primary sources and collected through interviews. The results of this study showed that partially, the Organizational Commitment variable significantly influences the Organizational Commitment variable, where the Interpersonal Communication Variable (3.327 2.021) and for the Organizational Commitment variable, the value is (3.209 2.021). Simultaneously, the Interpersonal Communication and Organizational Commitment variables significantly affect employee performance, with a value (12.371 2.84). Based on the determination coefficient calculation of 61.8%, Employee Performance (the dependent variable) can be explained by the Interpersonal Communication and Organizational Commitment variables. The remaining 55.1% is influenced by other factors not expounded in this research.